Motivation of extended behaviors by anterior cingulate cortex. - Holroyd, C; Yeung, N (2012)
Intense research interest over the past decade has yielded diverse and often discrepant theories about the function of anterior cingulate cortex (ACC). In particular, a dichotomy has emerged between neuropsychological theories suggesting a primary role for ACC in motivating or 'energizing' behavior, and neuroimaging-inspired theories emphasizing its contribution to cognitive control and reinforcement learning. To reconcile these views, we propose that ACC supports the selection and maintenance of 'options' - extended, context-specific sequences of behavior directed toward particular goals - that are learned through a process of hierarchical reinforcement learning. This theory accounts for ACC activity in relation to learning and control while simultaneously explaining the effects of ACC damage as disrupting the motivational context supporting the production of goal-directed action sequences.